PENGETAHUAN ORANG TUA TENTANG PENTINGNYA PEMERIKSAAN MATA SEJAK DINI PADA ANAK DI RW 05 DESA GALANGGANG KECAMATAN BATUJAJAR KABUPATEN BANDUNG BARAT - sekar Laras, dwi; Nurul Aini, Delia; pamungkas, Motris (Sekolah Tinggi Ilmu Kesehatan Dharma husada, 2024)
Eye health examination is a crucial component of children's overall health assessment. Early eye examination plays a significant role in detecting and preventing vision loss or visual impairments in children. Therefore, it is vital for parents to understand the importance of eye examinations and proper eye care for their children. This study aims to assess Parents' Knowledge About the Importance of Early Eye Examination in Children at RW 05, Galanggang Village, Batujajar District, West Bandung Regency. The research employed a descriptive quantitative method with a cross-sectional approach. Primary data were collected through questionnaires. The study sample comprised 83 respondents. Findings reveal that, among the 83 respondents, parental knowledge regarding the importance of early eye examination in children is categorized as